2013
DOI: 10.1161/circulationaha.113.001969
|View full text |Cite
|
Sign up to set email alerts
|

AMG145, a Monoclonal Antibody Against Proprotein Convertase Subtilisin Kexin Type 9, Significantly Reduces Lipoprotein(a) in Hypercholesterolemic Patients Receiving Statin Therapy

Abstract: L ipoprotein(a) [Lp(a)] is a circulating lipoprotein composed of an apolipoprotein B100 (ApoB) molecule covalently bound to a liver-derived glycoprotein, apolipoprotein(a) [Apo(a)].1 Apo(a) is encoded by the LPA gene on chromosome 6and shares structural homology with plasminogen. 2 Lp(a) is postulated to play a role in tissue healing and innate immunity, but its precise physiological role remains undefined.3 It is increasingly recognized as having both proatherosclerotic and prothrombotic Background-Lipoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 157 publications
(60 citation statements)
references
References 33 publications
8
52
0
Order By: Relevance
“…This observation is consistent with the dose‐response relationship observed in the phase 2 MENDEL and LAPLACE studies, where the 140‐mg Q2W dose of evolocumab approached the flat upper part of the dose‐response curve 5, 31. For example, in the LAPLACE study, a 30% increase in evolocumab dose from 105 mg SC Q2W to 140 mg SC Q2W resulted in an additional ∼5% reduction in LDL‐C at week 12 5. As a consequence, changes to the LDL‐C‐lowering effect are relatively insensitive to changes in pharmacokinetics.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This observation is consistent with the dose‐response relationship observed in the phase 2 MENDEL and LAPLACE studies, where the 140‐mg Q2W dose of evolocumab approached the flat upper part of the dose‐response curve 5, 31. For example, in the LAPLACE study, a 30% increase in evolocumab dose from 105 mg SC Q2W to 140 mg SC Q2W resulted in an additional ∼5% reduction in LDL‐C at week 12 5. As a consequence, changes to the LDL‐C‐lowering effect are relatively insensitive to changes in pharmacokinetics.…”
Section: Discussionsupporting
confidence: 88%
“…The timing and magnitude of LDL‐C lowering after a dose of evolocumab were consistent with those seen in other studies in patients and healthy volunteers 5, 6, 8, 17, 31. For example, the randomized, double‐blind, placebo‐controlled, phase 2 MENDEL study showed that monotherapy with evolocumab 140 mg Q2W in 45 patients with hypercholesterolemia (baseline LDL‐C 3.6 mmol/L) reduced LDL‐C from baseline by 51% (95% CI –56% to –46%) after 12 weeks of treatment 31.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…PCSK9 binds to the LDL-receptor thereby making it to a target of lysosomal degradation. Inhibitors of PCSK9 decrease Lp(a) levels up to 32% 16 and belong to the very promising drugs for future lipid-lowering therapies in case it will be demonstrated that they also lower clinical endpoints. Therapies that have a significant Lp(a)-lowering effect result in many cases also in substantial changes of other risk factors.…”
Section: February 11 2014mentioning
confidence: 99%